PENGARUH TINGKAT PENGETAHUAN TERHADAP KEPATUHAN MINUM OBAT PADA PASIEN TUBERCULOSIS DI PUSKESMAS JAYANTI TAHUN 2021 - Putri Rismawati (Nusantara Hasana Journal, 2023)
Tuberculosis (TB) is still the biggest health problem in the world, one of which is in developing countries including Indonesia. Based on the background of the problem obtained is the lack of public knowledge of tuberculosis, because this disease is susceptible to transmission through air droplets, while there is a lack of medication adherence for tuberculosis patients who are advised to take anti-tuberculosis drugs for 6 months without breaking. The data for Tuberculosis disease that occurred at the Jayanti Public Health Center with a population of 85512 and an estimated Tuberculosis case in 2020 with a total of 216 people, the total number of patients being treated was 120 people, with a cure rate that had not been achieved from the results of the data obtained that there were tuberculosis patients who were not treated. There are 11 people who are obedient to taking medication, it is possible that the patient did not comply with taking medication because of individual factors who felt that the patient had recovered enough and there was a lack of knowledge about the treatment of tuberculosis. Research Methods in this study using a cross sectional approach. The population is tuberculosis patients who are at the Jayanti Public Health Center with a total of 216 and a sample of 140 respondents is obtained. The sampling technique in this study was using purposive sampling. The results showed that there was an effect of knowledge on medication adherence in tuberculosis patients, with chisquare p value of 0.000 < 0.05. There was an effect of knowledge on drug adherence in tuberculosis patients.